Analisis Manajemen Perawatan Komponen Kritis Lampu APILL Tenaga Surya di Kota Yogyakarta dengan Pendekatan Reliability Centered Maintenance (Studi Kasus di PT Qumicon Indonesia) - Famelga Clea Putri (Metode : Jurnal Teknik Industri, 2023)
PT Qumicon Indonesia is a company engaged in the procurement of signs and other traffic equipment. In addition to procuring goods, PT Qumicon Indonesia also provides services for the maintenance of several products produced by the company, one of which is the solar powered APILL lamp. In this study, the company has not implemented a preventive maintenance approach in the maintenance of solar-powered APILL lamps in the city of Yogyakarta because PT Qumicon Indonesia will only carry out maintenance when there has been a call or request from the Provincial Transportation Office regarding damage and so on (corrective maintenance). In addition, the problem that is the object of research is that PT Qumicon Indonesia does not have a schedule to carry out preventive maintenance. From suggestions for improving the decision to carry out maintenance activities or replacing components in order to achieve 80% reliability, the battery which is the most critical component at 6 intersections in the city of Yogyakarta is checked regularly. Melia Purosani SP4 battery components are checked every 240 hours or 8 days, BO Plaza SP3 battery components are checked every 305 hours or 12 days, Gramedia SP4 battery components are checked every 434 hours or 18 days, Tugu SP4 battery components are checked every 338 hours or 14 days, the Jati Kencana SP4 battery components are checked every 270 hours or 11 days, and the Garuda SP4 battery components are checked every 305 hours or 12 days. From the results of the Failure Mode and Effect Analysis (FMEA) analysis, it is obtained that for the RPN value factor, the number of failures, and the reliability value, what needs to be considered so that system failure does not occur is the subsystem on the battery, the program IC on the controller, the program IC on the slave controller, and the terminal driver cable on the RF Transceiver.